1999
DOI: 10.1071/ah990056a
|View full text |Cite
|
Sign up to set email alerts
|

A review of the role of information technology in discharge communications in Australia

Abstract: Information technology is believed to be useful for the communication of discharge information between hospitals and community-based health practitioners. At least 20 projects were conducted in Australia between 1993 and 1997 to explore this idea. The value of these projects was at least $618,000. Despite this level of activity there is no good evidence, either from these projects or the international literature, to suggest that information technology can improve the quality of discharge communications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…In a more recent review on effects of electronic communication in general practice, only a few studies reported improvements over paper communications (van der Kam, Moorman, & Koppejan‐Mulder, 2000). An Australian study of discharge communications finds no good evidence to suggest that information technology could improve the quality of these communications between hospitals and primary care (Bolton, 1999).…”
Section: Health Systems Professionals and Patientsmentioning
confidence: 99%
“…In a more recent review on effects of electronic communication in general practice, only a few studies reported improvements over paper communications (van der Kam, Moorman, & Koppejan‐Mulder, 2000). An Australian study of discharge communications finds no good evidence to suggest that information technology could improve the quality of these communications between hospitals and primary care (Bolton, 1999).…”
Section: Health Systems Professionals and Patientsmentioning
confidence: 99%